Black female vampires in African American women's novels, 1977-2011 : she bites back - Parker, Kendra R. (Lexington Books, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2019)
This book critically situates the figure of the black female vampire within literary studies, cultural studies, gender studies, and critical race studies. It invites readers to take a closer look at the black female vampire figure and how that figure shapes and is shaped by cultural narratives about African American womanhood.